2022
DOI: 10.1007/s12350-021-02603-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of cardiac fibroblast activation in a patient after acute myocardial infarction using 68Ga-FAPI-04

Abstract: Our previous study has demonstrated the feasibility of noninvasive imaging of fibroblast activation protein (FAP)-expression after myocardial infarction (MI) in MI-territory in a rat model with 68Ga-FAPI-04-PET. In the current extended clinical case, we sought to delineate cardiac uptake of 68Ga-FAPI-04 in a patient after MI with clinical indication for the evidence of fibroblast activation. Carcinoma patients without cardiac disease underwent 68Ga-FAPI-04-PET/CT as control. The patient with one-vessel disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 18 publications
(25 reference statements)
0
33
0
Order By: Relevance
“…Reperfused MI induced an extending FAPI uptake over the infarct region Previous reports [12,14] demonstrated an extended broblasts activation over the perfusion defect and LGE area. In the current study, by comparing with multiple CMR sequences, we further identi ed that the FAPI uptake extent was even larger than the edematous area.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Reperfused MI induced an extending FAPI uptake over the infarct region Previous reports [12,14] demonstrated an extended broblasts activation over the perfusion defect and LGE area. In the current study, by comparing with multiple CMR sequences, we further identi ed that the FAPI uptake extent was even larger than the edematous area.…”
Section: Discussionmentioning
confidence: 75%
“…Using gallium-68 ( 68 Ga)-labeled FAPI, Varasteh and coworkers demonstrated excellent in vivo imaging quality for the detection of post-MI broblast activation in a MI rat model [11]. More recently, the feasibility of 68 Ga-FAPI imaging in MI patients was reported by Notohamiprodjo [12], Kessler [13], and Diekmann [14], which identi ed intense FAPI uptake in the infarcted territory. These data suggest that FAPI imaging is a reliable technique in delineating the temporospatial status of activated broblasts and may help to better explain post-MI pathophysiologic evolution and monitoring of the e cacy of anti brotic therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also revealed that most of the uptake was in the border-ischemic area [61]. FAPI accumulated beyond the extent of the infarcted zone, thereby revealing a tendency to overestimate the infarct size [62]. However, this may be caused by a remodeling in the peri-infarct zone as a result of perfusion deficits also in this area.…”
Section: Cardiovascular Diseasementioning
confidence: 66%
“…FAP inhibitor (FAPI) tracers were initially developed as theranostic ligands for metastasized cancer. Recently, they have been used to study cardiac remodeling following MI in small-animal models [59] and in humans (Figure 3) [60,61]. The tracers were also used to investigate cardiac remodeling in patients who underwent FAPI PET imaging for cancer staging [62][63][64], in patients with a checkpoint inhibitor (ICI)-associated myocarditis [65], with nonischemic dilated cardiomyopathy [66], and to image cardiotoxicity in patients after receiving systemic cancer therapy [67].…”
Section: Fibrosis and Fibrosis Activitymentioning
confidence: 99%